Pediatric Airway Foreign Body Training Experience - Garrett Griffin; Rebecca Hoesli; Marc Thorne (Association of American Medical Colleges, 2013)
Abstract Pediatric airway foreign body is a relatively rare but potentially life-threatening event. A significant proportion of foreign body aspirations are unwitnessed, and there are often few early symptoms after the initial coughing/gagging episode. Hence, practitioners must have a high index of suspicion for this diagnosis in any child that presents after such an event. Initially undiagnosed airway foreign body can present later with new or atypical wheezing, cough, stridor, or pneumonia. Once diagnosed, safe removal of a pediatric airway foreign body requires effective communication and coordination between the surgeon, OR staff, and anesthesiologist. This module includes a simulation case, pre- and posttests, an instructional PowerPoint presentation, and case and performance evaluations. The amount of time required to complete the case will vary with the experience of the participant. Junior residents averaged 90 minutes and senior residents 75 minutes in the authors' experience. Fellows and attending physicians may need just 45-60 minutes. This training experience has been successfully employed to train junior and senior otolaryngology residents in the cognitive, procedural, and interpersonal skills required to manage a pediatric airway foreign body. A study confirming face and construct validity for the case has been published and is included in the reference materials. This study included 7 junior and 5 senior otolaryngology trainees, and was administered by two otolaryngology faculty. In July 2012, the simulation was additionally administered by a group of 5 pediatric otolaryngology faculty to a new group of 16 otolaryngology residents during a weekend Otolaryngology Simulation course. The pediatric airway foreign body simulation is now performed with all junior otolaryngology residents at the University of Michigan at the beginning of their first pediatric otolaryngology rotation. This improves patient safety, teaches critical fundamentals of pediatric bronchoscopy, and allows trainees to make better use of operating room time with live patients.